Proteomics: From Protein Sequence to Function
Following the announcement of the draft sequence of the humangenome and the completion of many others, attention is now turning to theanalysis of the proteins encoded by the genome. This is a rapidly developingresearch area and Proteomics: From Protein Sequence To Function reviews recentdevelopments in proteomics and compares them with current genomics technologies.This book is written by written by experts from academia and industry, whoreview their area in a concise yet easy to understand style providingcomprehensive coverage integrating genomics with proteomics. The book will appeal to undergraduate in biochemistry, molecularbiology and genetics and all postgraduates and researchers with an interest ingenomics and protemics.